Sensitive Detection of Sulfide Ion Based on Fluorescent Ionic Liquid–Graphene Quantum Dots Nanocomposite - Qiu, Guanhua; Han, Yaoqi; Zhu, Xiaoqi; Gong, Jiawei; Luo, Tao; Zhao, Chang; Liu, Junjie; Liu, Jiyang; Li, Xiang (Frontiers in Chemistry, 2021)
Sulfide ions (S2−) that are widely distributed in biological and industrial fields are extremely toxic and pose great harms to both ecological environment and human health. However, fluorescent sensors toward S2− ions commonly use S2−-recovered fluorescence of fluorophore that is first quenched mainly by metal ions. Fluorescent probe which enables direct, selective, and sensitive detection of S2− ion is highly desirable. Herein, we demonstrate one-step preparation of fluorescent ionic liquid–graphene quantum dots (IL-GQDs) nanocomposite, which can act as a fluorescent probe for direct and sensitive detection of S2− ion. The IL-GQDs nanocomposite is easily synthesized via facile molecular fusion of carbon precursor and in situ surface modification of GQDs by IL under hydrothermal condition. The as-prepared IL-GQDs nanocomposite has uniform and ultrasmall size, high crystallinity, and bright green fluorescence (absolute photoluminescence quantum yield of 18.2%). S2− ions can strongly and selectively quench the fluorescence of IL-GQDs because of the anion exchange ability of IL. With IL-GQDs nanocomposite being fluorescent probe, direct and sensitive detection of S2− is realized with a linear detection range of 100nM–10μM and 10μM–0.2mM (limit of detection or LOD of 23nM). Detection of S2− ions in environmental river water is also achieved.